The Role of the Ditreskrimum in Handling the Crime of Motor Vehicle Theft Perpetrated by Minors in the Riau Regional Police Legal Territory - Ainul Andri Lubis (Police Studies Review, 2021)
The focus of this thesis research is motivated by the phenomenon of the increase in motor vehicle theft committed by children in the jurisdiction of the Riau Police. Therefore, a study was conducted which aims to describe the general description motor vehicle theft by minors in the Riau Regional Police, to describe the role of Reskrim in handling criminal acts of criminal charges by minors in the Legal Territory of Polda Riau, as well as to find out the following factors: factors that can affect the role of Criminal Investigation Unit in dealing with motor vehicle theft by minors in the Legal Area of the Riau Police. The theory and concepts used by the writer in answering the problem are theft, prevention of crime, general overview of child protection, the concept of restorative justice, and management theory. This research was conducted with a qualitative approach and used a descriptive analysis type of research. The findings of this study are the factors causing the occurrence of curarmor crimes by minors, including economic aspects, socio-cultural aspects, and environmental factors. Parental poverty is the basis for triggering the crime of motor vehicle theft in the Riau Province Regional Police. The efforts of the Riau Police to minimize motor vehicle theft include preventive and oppressive measures. Factors that can affect the role of Reskrim in dealing with criminal offenses by minors in the Legal Area of the Riau Police include, the number of investigators and assistant investigators is still insufficient, the lack of good support for the operation of the equipment used for the survey becomes ineffective because it is not can be run. Based on the results of the research, the authors suggest that the need to pay attention to and handle all government agencies, especially the police which are more serious, comprehensive, planned and comprehensive in juvenile cases, especially cases involving minors, The role of the police (in this case this investigator) as a community partner must always be strengthened through direct access to the community plan in the handling and disclosure as well as the prevention and eradication of motor vehicle theft committed by minors, and there is a need to increase the vigilance and safety of every motorized vehicle owner or user.